Hypoglycemic and antihyperglycemic effects of Abelmoschus esculentus and Alchornea cordifolia in normal and alloxan-induced diabetic rats - Barnabé Lucien Nkono Ya Nkono; Adjia Hamadjida; Damolai Gounkagou; Fidèle Ntchapda; Sélestin Sokeng Dongmo; Pierre Kamtchouing (Elsevier, 2024)
Background: Abelmoschus esculentus and Alchornea cordifolia are commonly used in Traditional Chinese Medicine (TCM) to treat several diseases. Abelmoschus esculentus is used to treat infertility and menorrhagia, while Alchornea cordifolia is used for the treatment of venereal diseases, cough, and diarrhoea. However, very few studies assessed the antidiabetic effects of these plants. Therefore, this study aimed to investigate the hypoglycemic and antihyperglycemic effects of aqueous extract of A. esculentus fruits and A. cordifolia leaves. Material and Methods: Fresh Abelmoschus esculentus fruits and the powder from the dried leaves of Alchornea cordifolia leaves were prepared by maceration in the aqueous phase (200 mg/100 mL and 50 mg/100 mL respectively) for 24 h, then filtered and concentrated in an oven at 45 °C. Diabete was induced to male Wistar rats by a single intraperitoneal injection of alloxan (150 mg kg−1, b.w). Rats with a blood glucose level greater than or equal to 200 mg/dL were selected, divided into groups and were daily administered orally with either aqueous extracts of A. esculentus at 30 mg kg−1 (AEAE30) or A. cordifolia at 400 mg kg−1 (AEAC400) for 14 consecutive days. For comparison, acarbose (100 mg kg−1), glibenclamide (5 mg kg−1), and 500 mg kg−1 metformin (Glucophage) were administered orally as reference drugs. Moreover, insuline was also used as a positive control and administered intraperitoneally at a dose of 5 IU/kg. Then, blood glucose levels, oral glucose tolerance test, oral maltose tolerance club, body weight and hemoglobin were assessed. For evaluation of the aqueous extracts in the intestinal transit, imodium (2mg kg−1, p.o) and fructine (5 mg kg−1, p.o) were used as a positive control to determine the spasmolytic and laxative activities, respectively. The histopathological study of the liver, kidney, pancreas, testis, epididymis, and seminal vesicle was also carried out using the hematoxyline & eosin (H&E) technique. Results: AEAE30 and AEAC400 significantly reduced (P < 0.001) fasting blood glucose (FBG) levels and significantly prevented (P < 0.001) postprandial glycemia in AI-db rats following oral glucose tolerance test (OGTT) and oral maltose tolerance test (OMTT) in alloxan-induced diabetic rats (AI-db). In normoglycemic and insulin-resistant (IR) rats, AEAE30 significantly prevented the post-prandial blood glucose level during the OGTT (P < 0.01) only in normoglycemic rats. At the end of treatment, AEAE30 significantly reduced the relative weight of the liver (P < 0.01) and significantly increased (P < 0.001) the relative weight of the testes and pancreas while AEAC400 significantly increased the relative weight of the testes compared to untreated AI-db rats. The histopathological study revealed a restoration of alloxan-induced tissue damage close to the normal control group in AI-db animals treated with plant extracts, as well as an increase in sperm density in the epididymis unlike in the untreated AI-db group. Conclusion: These findings suggested that AEAE and AEAC exhibited hypoglycemic and antihyperglycemic activities and could be therefore a useful source of antidiabetic agent.